The Beckman report on database research - Bernstein, Phil; Chaudhuri, Surajit; Gehrke, Johannes; al, et (Communications of the ACM, 2016)
Database researchers paint big data as a defining challenge. To make the most of the enormous opportunities at hand will require focusing on five research areas.